Technical, economic, and environmental feasibility assessment of solar-battery-generator hybrid energy systems: a case study in Nigeria - Ijeoma, Muzan Williams; Lewis, Christopher Garrett; Chen, Hao; Chukwu, Benjamin Nnamdi; Carbajales-Dale, Michael (Frontiers in Energy Research, 2024)
Supermarkets in Nigeria rely on diesel generators for electricity due to the unreliability of the national grid. The recent removal of petroleum subsidies in 2023 has increased fuel prices by 60%. This research examines the technical, economic, and environmental viability of employing solar PV/battery storage/generator systems to generate electricity for high-load supermarkets. The case study was conducted in the Market Square (MS) supermarket in Port Harcourt (PH) city, Nigeria. The MS supermarket had a load demand of 59.8 kW/day for an energy audit in 2022. The average solar radiation and temperature for PH city were 4.21 kWh/m2 and 25.3°C, respectively. The hybrid system was simulated with the HOMER Pro software. The simulation revealed that the optimum baseline (BL) system for the present price of a liter of diesel in Nigeria (0.63 USD/L) was a solar PV/Battery/Generator. The optimal BL system produced 401,599 kWh/year, which was more than adequate to cover the yearly load requirement of 204,765 kWh/year and left a surplus of 173,195 kWh/year. The BL system had a levelized cost of electricity of 0.106 USD/kWh, a net present cost of 232,533, and Operation and Maintenance cost of 7,928. When the overall environmental impact of the optimal BL system was assessed, it contributed 10,935 kg CO2-eq/year of global warming potential, 1,611 kg O3-eq/year of smog formation, and 72.2 kg SO2-eq/year of acidification potential to the environment. Sensitivity analysis shows that the BL system could have a net present value of 710,364, a 38% internal rate of return, and a 2-year simple payback period over a 25-year life if the excess energy is sold to the grid. Also, LCOE increases with fuel price or discount rate increase, while CO2 falls as all renewable hybrid system configurations become more advantageous. The potential reduction in CO2 emission in the proposed system highlights the environmental benefits compared to traditional ones. This finding will guide decisions on adopting hybrid energy solutions for supermarkets in Nigeria. This analysis offers crucial insights for energy sector decision-makers seeking to balance reliability, cost-effectiveness, and environmental sustainability in a volatile market.